2019
DOI: 10.1177/1049731519852150
|View full text |Cite
|
Sign up to set email alerts
|

How to Teach Evidence-Based Practice in Social Work: A Systematic Review

Abstract: Purpose: This article presents a systematic review of research regarding how best to educate social work students and practitioners concerning of the process of evidence-based practice and/or the application of empirically supported treatments (ESTs). Method: We conducted a systematic review with a narrative synthesis, largely following the Cochrane Handbook of Systematic Reviews for Interventions and PRISMA reporting guidelines for systematic reviews and meta-analyses. Results: Twenty-seven studies met our el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Considerable efforts have been made to enable attitude measurement in implementation science in order to better understand its contribution to implementation processes [ 14 16 ]. Knowledge on the other hand is a central construct in determinant frameworks–such as the Consolidated Framework for Implementation Research [ 17 ]–and has been highlighted in numerous studies as a persistent barrier to evidence uptake and implementation including healthcare [ 18 , 19 ], social welfare [ 20 , 21 ] and education [ 22 ]. It is therefore relevant to also consider the role of these two constructs for the work of ISPs.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been made to enable attitude measurement in implementation science in order to better understand its contribution to implementation processes [ 14 16 ]. Knowledge on the other hand is a central construct in determinant frameworks–such as the Consolidated Framework for Implementation Research [ 17 ]–and has been highlighted in numerous studies as a persistent barrier to evidence uptake and implementation including healthcare [ 18 , 19 ], social welfare [ 20 , 21 ] and education [ 22 ]. It is therefore relevant to also consider the role of these two constructs for the work of ISPs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, educational institutions have increasingly aimed to accommodate RSIs and EBP by, for example, adjusting academic or fieldwork curricula (Bertram et al, 2014, 2018; Drisko & Grady, 2019; Mennen et al, 2018). However, since the evidence on techniques for effectively teaching EBP remains scarce (Drisko & Grady, 2019; Spensberger et al, 2020), it is unlikely that such efforts alone will succeed in growing a much needed workforce of professionals who can progress a more widespread use of the EBP model in human and social service settings. Furthermore, it is well-documented in the literature that training, in the form of teacher-centered didactic education sessions, can be effective in building theoretical knowledge and shaping attitudes and beliefs, but it is often insufficient to achieve practical application of RSIs in real-world settings (Beidas & Kendall, 2010; Hecht et al, 2016; Prior et al, 2008).…”
mentioning
confidence: 99%
“…A Norwegian study (Finne et al, 2019) demonstrated that social workers rely more frequently on their colleagues than on research literature when making decisions in practice. Although research suggests that there is no conclusive evidence on the most effective way of teaching EBP (Spensberger et al, 2020), studies have demonstrated that teaching students to search for and use interventions increases both their familiarity with EBP and their ability to allocate evidence (Peterson et al, 2011). Based on previous literature and the results from the current study, we argue that if practitioners are to rely on research findings to inform their practice, they must first have an understanding of methodological design, and in particular a basic knowledge of statistical concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the importance of teaching EBP in social work education in order to increase favorable EBP attitudes and facilitate research into social work practices (Parrish & Rubin, 2011;Spensberger et al, 2020;Tennille et al, 2016). Moreover, the Council of Social Work Education emphasizes that "teaching social work students how to access, analyze, interpret, and appropriately employ evidence is critical to effective social work practice" (Council of Social Work Education, n.d.).…”
mentioning
confidence: 99%